Infusion rather than isolation: Integrating principles of equity, diversity, inclusion, decolonization, and Indigenization in toolkits for remote instruction during the COVID-19 pandemic - Karalyn McRae; Lauren Anstey; Lindsay Brant; Robin Attas (To Improve the Academy, 2023)
In the spring of 2020, our Centre for Teaching and Learning (CTL) developed the Transforming Teaching and Teaching Assistant Toolkits, consisting of in-house and curated open-access resources on various aspects of remote teaching, along with accompanying webinars. We deliberately infused principles of equity, diversity, and inclusion (EDI) and decolonization and Indigenization across all aspects of the resources for several reasons: our CTL’s commitment to these principles as institutional priorities that are the responsibility of all staff, numerous theorists’ advocacy to adopt inclusive pedagogies across the curriculum rather than tokenistic “add-and-stir” gestures, and a desire to counter the inequities in education and society at large re-exposed and perpetuated by the COVID-19 pandemic. We share our approach, explore its impact by outlining the toolkits’ design and delivery and by analyzing data from a survey of instructors who engaged with the toolkits, and propose some strategies for educational developers engaged in resource development to undertake their own infusion initiatives.